Fair-faced concrete for chimney of power plant and preparation method of fair-faced concrete

By using components such as shale ceramide and polydimethylsiloxane emulsion in clean water concrete for power plant chimneys, the problem of concrete cracking and peeling in high temperature and acidic environments is solved, efficient acid corrosion resistance and high temperature resistance are achieved, and self-cleaning function is given, which significantly reduces operating costs.

CN119899007AActive Publication Date: 2025-04-29CHINA CONSTRUCTION WESTERN CONSTRUCTION GROUP NO 8 (SHANGHAI) CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510402070.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-04-29
Estimated Expiration
2045-04-01

AI Technical Summary

Technical Problem

Existing concrete has cracked and peeled due to high temperature and acid corrosion in power plant chimneys, and lacks self-cleaning capabilities, which increases operating costs and poses safety risks.

Method used

A clean water concrete for chimneys of power plants is adopted, which includes cement, fly ash, metakaolin, coarse aggregate, machined sand, shale ceratops, polydimethylsiloxane emulsion and water reducing agent. Through the pre-wetting treatment of shale ceratops and the use of polydimethylsiloxane emulsion, the concrete's acid corrosion resistance and high temperature resistance are enhanced, and the concrete's self-cleaning function is given.

Benefits of technology

It significantly improves the acid corrosion resistance and high temperature resistance of concrete, realizes self-cleaning function, reduces post-maintenance costs, extends the service life of concrete, and improves reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses fair-faced concrete for a power plant chimney and a preparation method thereof, and belongs to the technical field of concrete materials. The invention aims to provide the fair-faced concrete for the chimney of the power plant and the preparation method of the fair-faced concrete. The fair-faced concrete can meet the special performance requirements of high temperature resistance, corrosion resistance and the like and has good apparent quality and self-cleaning capacity. The bare concrete for the chimney of the power plant is prepared from the following components per cubic meter: 285 to 305 kg of cement, 40 to 50 kg of coal ash, 25 to 35 kg of metakaolin, 931 to 961 kg of coarse aggregate, 740 to 780 kg of machine-made sand, 40 to 60 kg of shale ceramsite, 3.7 to 5.6 kg of polydimethylsiloxane emulsion, 4.1 to 4.5 kg of water reducing agent and 152 to 155 kg of mixing water. The preparation method comprises the following steps: soaking shale ceramsite in 9g / L TiO2 turbid liquid for 24h, taking out and draining; adding the cementing material, the metakaolin and part of the mixing water, and stirring; then adding the shale ceramsite and the coarse aggregate, and stirring; and finally, adding the machine-made sand, the residual mixing water, the polydimethylsiloxane emulsion and the water reducing agent, and fully stirring to obtain the concrete mixture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete materials, in particular to a kind of plain concrete for chimneys of power plants and a preparation method thereof. Background Art

[0002] With the continuous advancement of modern industrial technology, power plant chimneys, as important facilities for industrial waste gas emissions, have increasingly higher material performance requirements.

[0003] The concrete of power plant chimneys is exposed to high-temperature flue gas for a long time, which is prone to cracking and peeling due to thermal stress. Traditional concrete materials cannot withstand the erosion of high-temperature flue gas for a long time, which has become a key problem restricting the performance improvement of power plant chimneys.

[0004] Secondly, during the operation of the power plant chimney, it will be exposed to flue gas containing acidic gases. These gases combine with moisture to form a highly corrosive medium, causing serious chemical corrosion to the concrete. This corrosion not only weakens the strength and durability of the concrete, but also accelerates the corrosion of the steel bars, further threatening the overall stability of the chimney.

[0005] At the same time, since power plant chimneys are usually exposed to harsh environmental conditions, pollutants can easily corrode the surface of ordinary concrete, while the surface of plain concrete is smooth and dense, which can effectively reduce the adhesion and penetration of pollutants, meeting functional requirements while taking into account aesthetics and economy. However, traditional plain concrete currently lacks self-cleaning capabilities and requires regular manual cleaning or other maintenance methods, which not only increases operating costs but also may pose safety hazards.

[0006] Therefore, how to prepare concrete that meets the requirements of the physical structure performance of power plant chimneys has become a technical problem that needs to be solved urgently. At present, there is no patent involving the preparation technology of plain concrete for power plant chimneys. Although some patents can meet certain performance requirements of power plant chimney concrete, there are still obvious shortcomings:

[0007] For example, the Chinese invention patent (CN115124291A) discloses a high temperature resistant concrete and its preparation method: although the crack resistance of concrete is improved, acid corrosion and self-cleaning ability are not fully considered, and the actual needs of chimneys cannot be fully met. A high temperature resistant concrete is proposed, which includes the following components by mass: 200-250 parts of cement, 150-180 parts of fly ash, 80-100 parts of mineral powder, 800-1000 parts of volcanic rock, 400-450 parts of slag, 300-400 parts of coal-to-liquid, 300-600 parts of microsilica powder, 15-20 parts of water reducer, 300-400 parts of steel slag powder, 100-200 parts of titanium carbide silicon powder, 100-200 parts of ferrochrome slag, 4-8 parts of fiber, and 170-200 parts of water. Although the technical solution of this patent can alleviate the drastic changes in the concrete structure at high temperatures, reduce the occurrence of cracking, and stabilize the mechanical properties to a certain extent, it uses steel slag powder and ferrochrome slag, the concrete's acid corrosion resistance is poor, and there may be a risk of heavy metal dissolution polluting the environment.

[0008] Another example is a Chinese invention patent (CN117776655A) that discloses a high-titanium heavy slag sodium water glass acid-resistant and heat-resistant concrete and a preparation method, including: by weight ratio, water glass: sodium fluorosilicate: refractory mud: high-titanium heavy slag sand: high-titanium heavy slag crushed stone = 1: (0.15~0.18): (1.20~1.50): (2.00~2.30): (3.00~3.30). The high-titanium heavy slag sodium water glass concrete prepared by this patent has good acid and heat resistance, which can significantly improve the life of buildings in acidic media. However, water glass concrete is relatively brittle and is prone to cracks due to temperature changes or stress concentration, especially in high-temperature and high-corrosion environments such as chimneys. Cracks may lead to a decrease in acid resistance and heat resistance under long-term use conditions.

[0009] Another example is the Chinese invention patent (CN117550855A) which discloses a high-temperature resistant plain concrete. A high-temperature resistant plain concrete, the raw materials of which include the following components by weight: 148-173 parts of water, 380-445 parts of cement, 5.5-8.9 parts of water reducer, 590-697 parts of river sand, 1-150 parts of artificial sand, 946-1020 parts of crushed stone, 10-15 parts of silicon micropowder, 10-15 parts of sodium carbonate, 10-15 parts of silicon carbide, and 35-55 parts of high-temperature resistant materials. This patent can be used to prepare plain concrete with good high-temperature resistance and excellent surface quality, but the patent mentions the use of sodium carbonate, which may decompose at high temperatures to form sodium oxide, and further react with acidic gases to form sodium sulfate. Sodium sulfate crystallizes and expands inside the concrete, which may cause the concrete to crack, further aggravating the acid corrosion problem and resulting in poor acid corrosion resistance. Summary of the invention

[0010] The technical problem to be solved by the present invention is to provide a kind of clear concrete for power plant chimneys which can meet the performance requirements of high temperature resistance and acid corrosion resistance of chimney concrete in service state, and at the same time has excellent surface quality and self-cleaning function and a preparation method thereof.

[0011] The present invention provides a technical solution, a kind of plain concrete for power plant chimney, each cubic meter of which comprises the following components:

[0012] Cement: 285~305kg,

[0013] Fly ash: 40~50kg,

[0014] Metakaolin: 25~35kg,

[0015] Coarse aggregate: 931~961kg,

[0016] Machine-made sand: 740~780kg,

[0017] Shale ceramsite: 40~60kg, the shale ceramsite needs to be soaked in TiO2 suspension and then drained.

[0018] Polydimethylsiloxane emulsion: 3.7~5.6kg,

[0019] Water reducing agent: 4.1~4.5kg,

[0020] Mixing water: 152~155kg.

[0021] The invention discloses a plain concrete for a chimney of a power plant, wherein the metakaolin has a specific surface area of ​​650-700 m2 / kg, and the high specific surface area enables the metakaolin particles to effectively fill the micropores of cement stone, reduce the porosity and refine the pore size distribution, and the total content of highly active SiO2 and Al2O3 is ≥95%, and the mass ratio of SiO2 / Al2O3 is 1.1-1.2:1. The metakaolin has sufficient volcanic ash activity, can react with cement hydration products to generate dense calcium aluminum silicate gel, and improve the acid corrosion resistance and high temperature resistance of the concrete.

[0022] The invention discloses plain concrete for chimneys of power plants, wherein the shale ceramsite is 600-grade crushed stone-type shale ceramsite with a diameter of 5 to 10 mm, with continuous grading, a water absorption rate of 8.5% to 9.5%, and a porosity of 35% to 38%. The shale ceramsite is fired at high temperature and has excellent thermal stability. The strong water absorption rate and large porosity make it easy for a photocatalyst to adhere to the surface of the ceramsite to achieve loading, and the ceramsite can release internal moisture in the concrete after being pre-wetted, so as to compensate for the shrinkage of the concrete and prevent the cracking of the concrete.

[0023] The invention discloses plain concrete for chimneys of power plants, wherein the solid content of the polydimethylsiloxane emulsion is 45%-50%, which not only ensures the film-forming density to block the penetration of corrosive media, but also maintains the uniform dispersion of emulsion particles in the cement matrix, and the pH value is 6.5-8.0, which, on the one hand, avoids the destruction of the passivation film on the surface of the steel bar in the acidic environment, and on the other hand, inhibits the excessive hydrolysis and condensation reaction of the siloxane molecules under alkaline conditions.

[0024] The invention discloses a plain concrete for a chimney of a power plant, wherein the cement is 42.5-grade ordinary Portland cement; and the fly ash is Class C II fly ash.

[0025] The invention discloses plain concrete for chimneys of power plants, wherein the particle size of the coarse aggregate is 5-25 mm, and the gradation is continuous; the particle size of the machine-made sand is 0.16 mm-5 mm, the fineness modulus is 2.5-3.1, the MB value is less than 1.0, and the stone powder content is 5-8%.

[0026] The invention discloses plain concrete for chimneys of power plants, wherein the water reducing agent is a polycarboxylic acid high-performance admixture, the water reducing rate is not less than 25%, and the solid content is 15%.

[0027] The invention discloses plain concrete for a chimney of a power plant, wherein the water-cement ratio of the concrete is 0.41-0.42, and the sand ratio is 42%-43%.

[0028] Another technical solution provided by the present invention is a method for preparing plain concrete for a power plant chimney, comprising the following steps:

[0029] S1. Soak the shale ceramsite in a TiO2 suspension with a concentration of 9 g / L for 24 hours, then take it out and drain it to obtain shale ceramsite loaded with TiO2 in a saturated surface dry state;

[0030] S2. When adding materials, first add cementitious materials, metakaolin and 80% of water, stir for 1 minute, and prepare cement paste with a relatively high water-binder ratio;

[0031] S3, add coarse aggregate and moistened shale ceramsite, and stir thoroughly for 1 minute so that the cement paste can wrap the coarse aggregate and ceramsite and embed into the pores of the ceramsite;

[0032] S4. Add machine-made sand, the remaining water, polydimethylsiloxane emulsion and water reducing agent, stir thoroughly for 2 minutes, and finally obtain plain concrete for power plant chimney.

[0033] The difference between the present invention and the prior art is that the present invention has the following technical effects:

[0034] (1) The present invention soaks shale ceramsite in a TiO2 suspension for pre-wetting treatment, so that the photocatalytic active substance TiO2 is uniformly loaded on the surface of the ceramsite. During the setting and hardening process of concrete, the loaded TiO2 gradually migrates to the surface of concrete and is stably distributed, thereby giving the concrete excellent self-cleaning function. In practical applications, TiO2 can effectively decompose organic pollutants attached to the surface of concrete through photocatalysis, significantly reducing the subsequent maintenance costs and keeping the outer surface of chimney concrete clean at all times. Since shale ceramsite is fired at high temperature, its internal structure is dense and has excellent stability. It can maintain good physical and chemical properties under high temperature environment and is not easy to crack or peel due to thermal stress. Therefore, in high temperature environments such as chimneys, concrete mixed with shale ceramsite exhibits better high temperature resistance, can effectively avoid structural damage caused by thermal expansion, and further improve the service life and reliability of concrete. Moreover, ceramsite has a water return effect, which can continuously provide hydration for unhydrated cement or fly ash particles, so that the cement hydration degree is improved and more dense gel phases are generated, thereby preventing concrete from being eroded by sulfate and reducing the generation and development of microcracks.

[0035] (2) The present invention further improves the acid corrosion resistance and high temperature resistance of concrete by introducing metakaolin and internally doped polydimethylsiloxane emulsion. In terms of acid corrosion resistance, metakaolin fills the internal pores of concrete and forms a dense calcium aluminum silicate gel, thereby enhancing the impermeability and acid corrosion resistance of concrete from the inside, while polydimethylsiloxane emulsion migrates to the surface of concrete and forms a dense organic silicon film, thereby blocking the penetration of acidic substances from the outside. In terms of high temperature resistance, the combination of the two forms a "double protection inside and outside" mechanism, which significantly improves the overall acid corrosion resistance of concrete; in terms of high temperature resistance, metakaolin significantly improves the high temperature stability of concrete from the inside by virtue of its high melting point characteristics and the high temperature resistant minerals generated by secondary hydration reaction. At the same time, polydimethylsiloxane emulsion forms a dense silicon dioxide protective film after decomposition under high temperature conditions, which provides excellent thermal insulation and antioxidant protection for concrete from the outside. The two work together in a synergistic way, not only effectively reducing the damage of high temperature to the internal structure of concrete, but also significantly enhancing the thermal stability and resistance to thermal damage of chimney concrete under high temperature conditions. In addition, the fine particle effect of metakaolin can optimize the microstructure of concrete, reduce porosity, thereby reducing the thermal expansion and contraction stress caused by temperature changes and inhibiting the expansion of microcracks. The elastic film layer formed by polydimethylsiloxane emulsion can also effectively buffer the stress concentration of concrete when the temperature difference changes, further improve the crack resistance of concrete, and make it more durable and reliable under complex environmental conditions.

[0036] (3) In the technical scheme of the method for preparing plain concrete for power plant chimneys, shale ceramsite is soaked in a TiO2 suspension with a concentration of 9 g / L for 24 h and then taken out and drained to obtain shale ceramsite loaded with TiO2 in a saturated surface dry state, which not only wets the shale ceramsite but also introduces photocatalytic particles through the ceramsite loading method; first, cementitious materials, metakaolin and part of the mixing water are added and stirred to form a cement paste with a relatively high water-cement ratio, and then shale ceramsite and coarse aggregate are added and stirred to wrap the shale ceramsite and coarse aggregate with the cement paste, and the cement paste can be fully embedded in the pores on the surface of the shale ceramsite to form ceramsite with a relatively smooth surface, thereby improving the fluidity of the mixture and reducing the absorption of water by the shale ceramsite in the later stage, thereby improving the working performance of the mixture; finally, machine-made sand, remaining mixing water, polydimethylsiloxane emulsion and water reducer are added, and after sufficient stirring, a concrete mixture is obtained to ensure the uniformity of each component of the concrete. DETAILED DESCRIPTION

[0037] The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.

[0038] The raw materials in the following examples are as follows:

[0039] (1) Cement: 42.5 grade ordinary Portland cement;

[0040] (2) Fly ash: Class C, Grade II fly ash;

[0041] (3) Metakaolin: specific surface area 672m 2 / kg, the main component is silicon aluminum oxide, and its SiO2 and Al2O3 contents are 50.67% and 44.34% respectively;

[0042] (4) Coarse aggregate: particle size is 5~25mm, continuous grading, apparent density is 2700kg / m 3 ;

[0043] (5) Artificial sand: fineness modulus is 2.7, MB is 0.8, and stone powder content is 6.4%;

[0044] (6) Shale ceramsite: 5~10mm 600 grade crushed stone type shale ceramsite, continuous grading, water absorption rate 8.5~9.5%, porosity 35~38%;

[0045] (7) Polydimethylsiloxane emulsion: solid content 45%~50%, pH value 6.5~8.0;

[0046] (8) Water reducing agent: Use polycarboxylic acid high-performance water reducing agent with a water reducing rate of 25% and a solid content of 15%;

[0047] (9) Mixing water: ordinary tap water.

[0048] Example 1

[0049] The present invention discloses a kind of plain concrete for power plant chimney, each cubic meter of which comprises the following components:

[0050] Cement: 305kg,

[0051] Fly ash: 40kg,

[0052] Metakaolin: 25kg,

[0053] Coarse aggregate: 961kg,

[0054] Machine-made sand: 730kg,

[0055] Shale ceramsite: 40kg,

[0056] Polydimethylsiloxane emulsion: 5.6kg,

[0057] Water reducing agent: 4.1kg,

[0058] Mixing water: 152kg.

[0059] In this embodiment, the concrete sand ratio is 42%, the water reducing agent dosage is 1.1%, and the water-cement ratio is 0.41.

[0060] In addition, this embodiment also provides a method for preparing plain concrete for a power plant chimney, and the specific steps are as follows:

[0061] S1. Soak the shale ceramsite in a TiO2 suspension with a concentration of 9 g / L for 24 hours, then take it out and drain it to obtain shale ceramsite loaded with TiO2 in a saturated surface dry state;

[0062] S2. When adding materials, first add cementitious materials, metakaolin and 80% of water, stir for 1 minute, and prepare cement paste with a relatively high water-binder ratio;

[0063] S3, add coarse aggregate and moistened shale ceramsite, and stir thoroughly for 1 minute so that the cement paste can wrap the coarse aggregate and ceramsite and embed into the pores of the ceramsite;

[0064] S4. Add machine-made sand, the remaining water, polydimethylsiloxane emulsion and water reducing agent, stir thoroughly for 2 minutes, and finally obtain plain concrete for power plant chimney.

[0065] Example 2

[0066] The present invention discloses a kind of plain concrete for power plant chimney, each cubic meter of which comprises the following components:

[0067] Cement: 290kg,

[0068] Fly ash: 50kg,

[0069] Metakaolin: 30kg,

[0070] Coarse aggregate: 951kg,

[0071] Machine-made sand: 730kg,

[0072] Shale ceramsite: 50kg,

[0073] Polydimethylsiloxane emulsion: 4.6kg,

[0074] Water reducing agent: 4.1kg,

[0075] Mixing water: 154kg.

[0076] In this embodiment, the concrete sand ratio is 42%, the water reducing agent dosage is 1.1%, and the water-cement ratio is 0.41.

[0077] In addition, this embodiment also provides a method for preparing plain concrete for a power plant chimney, and the preparation method is the same as that in Embodiment 1.

[0078] Example 3

[0079] The present invention discloses a kind of plain concrete for power plant chimney, each cubic meter of which comprises the following components:

[0080] Cement: 285kg,

[0081] Fly ash: 50kg,

[0082] Metakaolin: 35kg,

[0083] Coarse aggregate: 951kg,

[0084] Machine-made sand: 750kg,

[0085] Shale ceramsite: 50kg,

[0086] Polydimethylsiloxane emulsion: 4.6kg,

[0087] Water reducing agent: 4.5kg,

[0088] Mixing water: 154kg.

[0089] In this embodiment, the concrete sand ratio is 43%, the water reducing agent dosage is 1.2%, and the water-binder ratio is 0.42.

[0090] In addition, this embodiment also provides a method for preparing plain concrete for a power plant chimney, and the preparation method is the same as that in Embodiment 1.

[0091] Example 4

[0092] The present invention discloses a kind of plain concrete for power plant chimney, each cubic meter of which comprises the following components:

[0093] Cement: 290kg,

[0094] Fly ash: 50kg,

[0095] Metakaolin: 30kg,

[0096] Coarse aggregate: 951kg,

[0097] Machine-made sand: 750kg,

[0098] Shale ceramsite: 50kg,

[0099] Polydimethylsiloxane emulsion: 3.7kg,

[0100] Water reducing agent: 4.5kg,

[0101] Mixing water: 155kg.

[0102] In this embodiment, the concrete sand ratio is 43%, the water reducing agent dosage is 1.2%, and the water-binder ratio is 0.42.

[0103] In addition, this embodiment also provides a method for preparing plain concrete for a power plant chimney, and the preparation method is the same as that in Embodiment 1.

[0104] Example 5

[0105] The present invention discloses a kind of plain concrete for power plant chimney, each cubic meter of which comprises the following components:

[0106] Cement: 285kg,

[0107] Fly ash: 50kg,

[0108] Metakaolin: 35kg,

[0109] Coarse aggregate: 941kg,

[0110] Machine-made sand: 750kg,

[0111] Shale ceramsite: 60kg,

[0112] Polydimethylsiloxane emulsion: 3.7kg,

[0113] Water reducing agent: 4.5kg,

[0114] Mixing water: 155kg.

[0115] In this embodiment, the concrete sand ratio is 43%, the water reducing agent dosage is 1.2%, and the water-binder ratio is 0.42.

[0116] In addition, this embodiment also provides a method for preparing plain concrete for a power plant chimney, and the preparation method is the same as that in Embodiment 1.

[0117] Comparative Example 1

[0118] A kind of plain concrete for power plant chimney without using metakaolin, comprising the following components per cubic meter:

[0119] Cement: 285kg,

[0120] Fly ash: 85kg,

[0121] Coarse aggregate: 941kg,

[0122] Machine-made sand: 750kg,

[0123] Shale ceramsite: 60kg,

[0124] Polydimethylsiloxane emulsion: 3.7kg,

[0125] Water reducing agent: 4.5kg,

[0126] Mixing water: 155kg.

[0127] In this comparative example, the concrete sand ratio is 43%, the water reducing agent dosage is 1.2%, and the water-cement ratio is 0.42.

[0128] In addition, this comparative example also provides a method for preparing plain concrete for power plant chimneys without using metakaolin, and the specific steps are as follows:

[0129] S1. Soak the shale ceramsite in a TiO2 suspension with a concentration of 9 g / L for 24 hours, then take it out and drain it to obtain shale ceramsite loaded with TiO2 in a saturated surface dry state;

[0130] S2. When adding materials, first add cementitious materials and 80% of water, stir for 1 minute, and prepare cement paste with a relatively high water-binder ratio;

[0131] S3, add coarse aggregate and moistened shale ceramsite, and stir thoroughly for 1 minute so that the cement paste can wrap the coarse aggregate and ceramsite and embed into the pores of the ceramsite;

[0132] S4. Add machine-made sand, the remaining water, polydimethylsiloxane emulsion and water reducing agent, stir thoroughly for 2 minutes, and finally obtain plain concrete for power plant chimney.

[0133] Comparative Example 2

[0134] A kind of plain concrete for chimney of power plant without using ceramsite, each cubic meter of which comprises the following components:

[0135] Cement: 285kg,

[0136] Fly ash: 50kg,

[0137] Metakaolin: 35kg,

[0138] Coarse aggregate: 1001kg,

[0139] Machine-made sand: 750kg,

[0140] Polydimethylsiloxane emulsion: 3.7kg,

[0141] Water reducing agent: 4.5kg,

[0142] Mixing water: 155kg.

[0143] In this comparative example, the concrete sand ratio is 43%, the water reducing agent dosage is 1.2%, and the water-cement ratio is 0.42.

[0144] In addition, this comparative example also provides a method for preparing plain concrete for power plant chimneys without using ceramsite, and the specific steps are as follows:

[0145] S1. When adding materials, first add cementitious materials, metakaolin and 80% water, stir for 1 minute, and prepare cement paste with a relatively high water-binder ratio;

[0146] S2. Add coarse aggregate and stir thoroughly for 1 minute so that the cement paste can cover the coarse aggregate;

[0147] S3, adding machine-made sand, the remaining water, polydimethylsiloxane emulsion and water reducing agent, stirring thoroughly for 2 minutes, and finally obtaining plain concrete for power plant chimney.

[0148] Comparative Example 3

[0149] A kind of plain concrete for power plant chimney without using polydimethylsiloxane emulsion, comprising the following components per cubic meter:

[0150] Cement: 285kg,

[0151] Fly ash: 50kg,

[0152] Metakaolin: 35kg,

[0153] Coarse aggregate: 941kg,

[0154] Machine-made sand: 750kg,

[0155] Shale ceramsite: 60kg,

[0156] Water reducing agent: 4.5kg,

[0157] Mixing water: 155kg.

[0158] In this comparative example, the concrete sand ratio is 43%, the water reducing agent dosage is 1.2%, and the water-cement ratio is 0.42.

[0159] In addition, this comparative example also provides a method for preparing plain concrete for power plant chimneys without using polydimethylsiloxane emulsion, and the specific steps are as follows:

[0160] S1. Soak the shale ceramsite in a TiO2 suspension with a concentration of 9 g / L for 24 hours, then take it out and drain it to obtain shale ceramsite loaded with TiO2 in a saturated surface dry state;

[0161] S2. When adding materials, first add cementitious materials, metakaolin and 80% of water, stir for 1 minute, and prepare cement paste with a relatively high water-binder ratio;

[0162] S3, add coarse aggregate and moistened shale ceramsite, and stir thoroughly for 1 minute so that the cement paste can wrap the coarse aggregate and ceramsite and embed into the pores of the ceramsite;

[0163] S4. Add machine-made sand, the remaining water and the water reducing agent, stir thoroughly for 2 minutes, and finally obtain the plain concrete for the chimney of the power plant.

[0164] Comparative Example 4

[0165] A conventionally prepared plain concrete for power plant chimneys includes the following components per cubic meter:

[0166] Cement: 285kg,

[0167] Fly ash: 50kg,

[0168] Metakaolin: 35kg,

[0169] Coarse aggregate: 941kg,

[0170] Machine-made sand: 750kg,

[0171] Shale ceramsite: 60kg,

[0172] Polydimethylsiloxane emulsion: 3.7kg,

[0173] Water reducing agent: 4.5kg,

[0174] Mixing water: 155kg.

[0175] In this comparative example, the concrete sand ratio is 43%, the water reducing agent dosage is 1.2%, and the water-cement ratio is 0.42.

[0176] In addition, this comparative example also provides a method for preparing a conventionally prepared plain concrete for a power plant chimney, and the specific steps are as follows:

[0177] S1. When feeding, first add coarse aggregate, machine-made sand and shale ceramsite and stir for 1 minute;

[0178] S3, add the gelling material and stir thoroughly for 1 minute;

[0179] S3. Add water and admixtures, stir thoroughly for 2 minutes, and finally obtain plain concrete for power plant chimneys.

[0180] Comparative Example 5

[0181] A conventional plain concrete includes the following components per cubic meter:

[0182] Cement: 285kg,

[0183] Fly ash: 85kg,

[0184] Coarse aggregate: 1001kg,

[0185] Machine-made sand: 750kg,

[0186] Water reducing agent: 4.5kg,

[0187] Mixing water: 155kg.

[0188] In this comparative example, the concrete sand ratio is 43%, the water reducing agent dosage is 1.2%, and the water-cement ratio is 0.42.

[0189] In addition, this comparative example also provides a method for preparing ordinary plain concrete, and the specific steps are as follows:

[0190] S1. When feeding, first add coarse aggregate and machine-made sand and stir for 1 minute;

[0191] S3, add the gelling material and stir thoroughly for 1 minute;

[0192] S3. Add water and admixtures, stir thoroughly for 2 minutes, and finally obtain plain concrete for power plant chimneys.

[0193] The performance tests were conducted on the concrete of Examples 1-2 and Comparative Examples 1-5. A 10 mg / L methylene blue aqueous solution was selected as the organic matter to be tested and covered on the surface of the photocatalytic concrete. Under the irradiation of ultraviolet light, the methylene blue solution was decomposed with the photocatalytic reaction. At the same time, the absorbance of the methylene blue aqueous solution was tested by an ultraviolet spectrophotometer, and the photocatalytic self-cleaning efficiency of the concrete was characterized according to the concentration change of the methylene blue solution. A high temperature test was conducted using a building material burning furnace, 600°C, with an overall heating rate of about 20°C / min. When the test block test temperature reached 600°C, it was kept warm for 3 hours. After the test, the heating equipment was turned off, and the compressive strength was tested after the test block naturally cooled to room temperature.

[0194] The sulfate corrosion resistance performance refers to the standard GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" to test the compressive strength corrosion resistance coefficient after 150 sulfate dry-wet cycles. The test results are shown in Table 1.

[0195] Table 1 Concrete performance test results

[0196]

[0197] In combination with all the embodiments, it can be seen that by a reasonable ratio of the components in the present invention, a kind of plain concrete for power plant chimneys can be obtained, and different fluidities can be obtained by adjusting the ratio of the components in the present invention according to the specific requirements of the project.

[0198] Combining Example 5 with Comparative Examples 1 to 3, it can be seen that when the metakaolin in the ratio of the present invention is lacking, the compressive strength, high temperature resistance and acid corrosion resistance of the concrete are reduced; when shale ceramsite is lacking, the fluidity and compressive strength of the concrete are improved, but the high temperature resistance and acid corrosion resistance are also reduced, and it is impossible to introduce photocatalytic particles by the loading method using the characteristics of large water absorption and porosity of ceramsite, and it is impossible to give the concrete self-cleaning properties by this convenient means; when polydimethylsiloxane emulsion is lacking, the high temperature resistance and acid corrosion resistance of the concrete are also reduced, and the degree of reduction is most obvious.

[0199] Combining Example 5 with Comparative Example 4, it can be seen that the preferred preparation process of the fair-faced concrete for power plant chimneys of the present invention can more fully stimulate the self-cleaning ability, high temperature resistance, acid corrosion resistance and other properties of the concrete in the present invention.

[0200] Combining Example 5 with Comparative Example 5, it can be seen that the plain concrete for power plant chimneys prepared by the present invention has stronger fluidity and fewer surface pores than conventional plain concrete. It has excellent high temperature resistance and acid corrosion resistance and also has self-cleaning ability, which can fully meet the aesthetic and functional requirements of concrete for power plant chimneys.

[0201] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A kind of plain concrete for power plant chimney, characterized by: Each cubic meter includes components: Cement: 285~305kg, Fly ash: 40~50kg, Metakaolin: 25~35kg, Coarse aggregate: 931~961kg, Machine-made sand: 740~780kg, Shale ceramsite: 40~60kg, the shale ceramsite needs to be soaked in TiO2 suspension and then drained. Polydimethylsiloxane emulsion: 3.7~5.6kg, Water reducing agent: 4.1~4.5kg, Mixing water: 152~155kg.

2. The plain concrete for power plant chimney according to claim 1, characterized in that: The specific surface area of ​​the metakaolin is 650-700 m2 / kg, the total content of highly active SiO2 and Al2O3 in the metakaolin is ≥95%, and the mass ratio of SiO2 / Al2O3 is 1.1-1.2:

1.

3. The plain concrete for power plant chimney according to claim 1, characterized in that: The shale ceramsite is 600-grade crushed stone-type shale ceramsite with a size of 5 to 10 mm, continuous grading, a water absorption rate of 8.5% to 9.5%, and a porosity of 35 to 38%.

4. The plain concrete for power plant chimney according to claim 1, characterized in that: The polydimethylsiloxane emulsion has a solid content of 45% to 50% and a pH value of 6.5 to 8.

0.

5. The plain concrete for power plant chimney according to claim 1, characterized in that: The cement is 42.5 grade ordinary Portland cement; the fly ash is Class C Grade II fly ash.

6. The plain concrete for power plant chimney according to claim 1, characterized in that: The particle size of the coarse aggregate is 5-25 mm, with continuous grading; the particle size of the machine-made sand is 0.16 mm-5 mm, the fineness modulus is 2.5-3.1, the MB value is less than 1.0, and the stone powder content is 5-8%.

7. The plain concrete for power plant chimney according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid high performance water reducing agent with a water reduction rate of not less than 25% and a solid content of 15%.

8. The plain concrete for power plant chimney according to claim 1, characterized in that: The water-cement ratio of concrete is 0.41~0.42, and the sand ratio is 42%~43%.

9. A method for preparing plain concrete for power plant chimneys, characterized in that: The following steps are involved: S1. Soak the shale ceramsite in a TiO2 suspension with a concentration of 9 g / L for 24 hours, then take it out and drain it to obtain shale ceramsite loaded with TiO2 in a saturated surface dry state; S2. When adding materials, first add cementitious materials, metakaolin and 80% water, stir for 1 minute, and prepare cement paste; S3, add coarse aggregate and moistened shale ceramsite, and stir thoroughly for 1 minute so that the cement paste can wrap the coarse aggregate and ceramsite and embed into the pores of the ceramsite; S4. Add machine-made sand, the remaining water, polydimethylsiloxane emulsion and water reducing agent, stir thoroughly for 2 minutes, and finally obtain plain concrete for power plant chimney.

Citation Information

Patent Citations

  • High-temperature-resistant concrete and preparation method thereof

    CN115124291A

  • High-temperature-resistant fair-faced concrete

    CN117550855A

  • High-titanium heavy slag sodium silicate acid-resistant and heat-resistant concrete and preparation method thereof

    CN117776655A

  • Self-cleaning outdoor artificial stone plate and preparation method thereof

    CN110713360A

  • High-temperature-resistant concrete based on iron tailings and steel slag powder

    CN112851264A